Nondestructive Evaluation and Reliability Analysis for Determining the Mechanical Properties of Old Wood of Ancient Timber Structure - Yongping Chen; Wenjing Guo (BioResources, 2017)
The objective of this study was to evaluate the mechanical properties of ancient wood of Abies fabri (Mast.) Craib based on the nondestructive tests and reliability analysis. Nondestructive tests including resistograph and stress wave test, and destructive tests were conducted on the wood specimens. Results indicated that there were significant linear correlations between the resistance amplitude (F) and green density (ρ), the dynamic modulus of elasticity (ED) and static modulus of elasticity (MOE), modulus of rupture (MOR), and ultimate compressive strength (UCS) of wood specimens. The cumulative distribution of the predicted MOR and UCS based on the nondestructive tests could be well fitted by the normal distribution according to the χ2 test. Moreover, a reliability analysis program based on the first-order second-moment method was developed. Reliability analysis results showed that the reliability index increased nonlinearly with the increase of the live-to-dead load ratio, and decreased nonlinearly with the increase of the design values for all the simulation load cases. According to the minimum reliability index requirements of the Chinese national standard, it is suggested that the design value of MOR and UCS be 14.0 and 10.7 MPa, respectively.